2020
DOI: 10.2478/ttj-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Active Travel in Health and Quality of Life

Abstract: AbstractThe ever-increasing tendency of people to travel by motorized vehicles contributes significantly to air pollution and traffic problems. Active travel, namely walking and cycling, seems to be a feasible solution to the current situation in urban mobility. The present paper aims at investigating the effects of active travel in health and quality of life and determine those factors that affect travel behavior. A structured literature review was carried out, which revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…However, the effect of neighborhood characteristics on health and quality of life through transport-related physical activity levels was not found. This result was not in line with previous findings showing that transport-related physical activity was associated with health and quality of life ( 27 , 37 , 38 ). The variation in finding may be attributed to the fact that transport-related physical activity levels in the current study did not have enough variability to have any meaningful relationship with the participants' health and quality of life.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the effect of neighborhood characteristics on health and quality of life through transport-related physical activity levels was not found. This result was not in line with previous findings showing that transport-related physical activity was associated with health and quality of life ( 27 , 37 , 38 ). The variation in finding may be attributed to the fact that transport-related physical activity levels in the current study did not have enough variability to have any meaningful relationship with the participants' health and quality of life.…”
Section: Discussioncontrasting
confidence: 99%
“…Pucci et al ( 26 ) also found that there is a positive association between leisure-time physical activity and general quality of life. A study conducted by Adamos et al ( 27 ) showed that participants stated that walking in their daily traveling makes them happy and offers a lot of benefits to their health and they related significantly walking for travel with quality of life. However, Jurakić et al ( 28 ) found an inverse relation between transport-related physical activity and quality of life.…”
Section: Conceptual Frameworkmentioning
confidence: 99%